The influence of social networking, video games and general computer usage on parent-child relations (Fields)
The aim of this project was to find out how parents feel about controlling the media/technology use of their adolescent children and how it influences their parent/child relations. This is important because modern entertainment technologies are easily accessible and available to the population; thus they inevitably invade family space and influence family life. A gap in the literature is identified, indicating that existing research does not explore the reasons why parents control or do not control their adolescent children’s use of social media, video games and more. Additionally, there was no literature concerning how parents feel about such control and whether it was part of emotional labour; that being any activities that are performed with a child’s well-being in mind. The project was carried out as the part of an undergraduate degree course by the final year student in sociology. The data was collected through face-to-face and telephone semi-structured interviews with mothers and fathers of adolescents. It was observed that both mothers and fathers felt their control over children’s use of media and technologies influenced their relations. Also the findings show a variety of reasons why parents choose to exercise their control in a particular way, and how it links to parent-child relations.